Antimicrobial microneedle patch for treating deep cutaneous fungal infection - Zan, Ping (2021)
Subcutaneous fungal infection is often difficult to be treated by the conventional topical application or oral intake of antifungal agents because of low drug bioavailability to the infection site, lack of sustained therapeutic effect, and development of drug resistance. Here, a new strategy using polymeric microneedle (MN) patches to overcome the skin barrier is reported. MN is made of a biocompatible and biodegradable chitosan–polyethylenimine copolymer, which possesses antimicrobial property immune to drug resistance and allows sustained drug release. Using a fungal infection mouse model, it is demonstrated that MN patches encapsulated with antifungal agent amphotericin B offer outstanding treatment effectiveness. It is attributable to the high bioavailability of therapeutics and synergistic actions of the antifungal polymer and drug.